2020
DOI: 10.1503/cmaj.200647
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of antiviral treatment for COVID-19 from evidence in studies of SARS-CoV-2 and other acute viral infections: a systematic review and meta-analysis

Abstract: 1 has resulted in more than 3 million cases and more than 210 000 deaths worldwide. 2 The World Health Organization (WHO) has declared the COVID-19 outbreak a pandemic. The pathogen, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 3 is a novel Betacoronavirus that shares a phylogenetic similarity to SARS-CoV (about 79%) and Middle East respiratory syndrome (MERS)-CoV (about 50%). 4,5 Many clinical trials of potential COVID-19 treatments are underway, but current strategies for treatment are based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 45 publications
(88 reference statements)
1
67
0
3
Order By: Relevance
“…Another cases serie collected in China confirm that half of patients suffered digestive adverse effect and 7/10 patients showed hypokalemia [ 68 , 69 ]. Two recent meta-analyses [ 74 , 75 ] evaluating efficacy and safety of the most frequently used therapies for COVID-19 show as most of the AEs rate were comparable across the intervention and control groups. Conversely, LPV/r alone showed trend to more diarrhea events, while the combination of LPV/r, ribavirin and corticosteroids reduced incidence of diarrhea significantly.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Another cases serie collected in China confirm that half of patients suffered digestive adverse effect and 7/10 patients showed hypokalemia [ 68 , 69 ]. Two recent meta-analyses [ 74 , 75 ] evaluating efficacy and safety of the most frequently used therapies for COVID-19 show as most of the AEs rate were comparable across the intervention and control groups. Conversely, LPV/r alone showed trend to more diarrhea events, while the combination of LPV/r, ribavirin and corticosteroids reduced incidence of diarrhea significantly.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…There has been considerable controversy about the effects of hydroxychloroquine, which inhibits SARS-CoV-2 replication in vitro 5 , but fails clinically to clear SARS-CoV-2 and to improve Covid-2, at least in hospitalized patients [6][7][8][9] . Hydroxychloroquine is a prototypic lysosomotropic agent, meaning that, due to its lipophilicity (at neutral pH) and low TPSA, it attains the cytoplasm and then enriches in the acidic environment of lysosomes because it is protonated and hence trapped within the lysosomal lumen.…”
Section: Lysosomotropic Versus Non-lysosomotropic Sars-cov-2 Antiviramentioning
confidence: 99%
“…However, they did not report on specific adverse events. Other systematic reviews found an increase in the risk of diarrhoea and nausea and/or vomiting with lopinavir-ritonavir 37,38 and hydroxychloroquine, [38][39][40] increase in arrhythmias and QTc interval prolongation with hydroxychloroquine alone, [40][41][42] or combined with a macrolide, 43,44 and no significant increase in renal failure with remdesivir. 45…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%